The relationship between trunk kinematic variables and underwater undulatory swimming performance in competitive swimmers - Tanaka, T.; Sato, T.; Hashizume, S.; Shiozawa, N.; Isaka, T. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to examine the relationship between selected trunk kinematic variables and undulatory underwater swimming performance in competitive swimmers. Eight male and 2 female swimmers performed 15 m UUS with their maximum efforts. Three-dimensional coordinate of markers attached to bony configurations were corrected during Pearson`s product moment by using the underwater motion capture system. The range of motion and the corresponding angular velocity were computed for lower waist, upper waist and chest. The relationship between horizontal velocity of center of mass and each kinematic variable was then examined. No significant correlations were found between horizontal velocity and each range of motion. The horizontal velocity was significantly correlate with the angular velocity of lower waist and of chest, but not with the corresponding value of upper waist. The current results suggest that the swimmers produce the great horizontal velocity by increase in trunk angular velocities rather than by increase in trunk range of motion.